IMPLEMENTATION OF DEMOCRATIC AND HUMANISTIC ISLAMIC EDUCATION IN SCHOOLS - Sri Haryanto (Penelitian dan Pengembangan Ilmu, 2024)
The research is descriptive qualitative research with a library research approach. Qualitative methods are used to explore and collect theoretical data by selecting literature that supports and is relevant to the object under study. The data obtained will then be analyzed using descriptive analytical techniques. It is believed that democratic and humanistic education will bring better changes in educational practice and can improve the quality of educational output, as well as being a solution to various current educational problems. Democratic and humanistic education also has great potential to create a generation of people who are intellectually intelligent, emotionally intelligent and spiritually intelligent, have a big soul, are active, creative, and are able to overcome the various life problems they face wisely and judiciously. This article provides an overview of how to actualize and implement democratic and humanistic Islamic education. It is hoped that the implementation of democratic and humanistic Islamic education can have a positive impact in forming the nation's young generation who are open-minded, critical, humanist and able to play an active role in society.